Kedudukan Lembaga Kepresidenan Untuk Mewujudkan Sistem Pemerintahan Yang Demokratis Berdasarkan UUD NRI 1945 - Selvy Anugrah Maharani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to discuss the implementation of a democratic system within the presidential institution using a literature study approach. The findings and discussions in this research explain an event analyzed by the researcher based on previous literature studies that have been examined by earlier scholars. The results of this study indicate that Indonesia, as a constitutional state, implements a clear division of power among state institutions to ensure stability in governance. This principle of the rule of law is not only applied in Indonesia but is also a widely accepted concept in many countries worldwide. The establishment of state institutions is based on legitimate authority as stipulated by law, with the President holding a strategic role as the head of state, as regulated in the 1945 Constitution of the Republic of Indonesia. This study concludes that to maintain a democratic system of governance, a well-structured administrative framework is necessary, emphasizing government accountability. This ensures that every policy and action taken is always based on legal principles and carried out transparently and responsibly.